231 Laparoscopic Cholecystectomy in Ambulatory: What Results? - Goulart, André (2013)
Introduction: Laparoscopic cholecystectomy is the gold standard procedure for the treatment of lithiasic gallblader pathology and acute cholecystitis. Whether or not it should be done as ambulatory surgery is still being discussed. The present study aims to analyze the quality and safety of laparoscopic cholecystectomy conducted by the Ambulatory Unit of Hospital de Braga and compare the results with those from other European surgical centers performing LC as ambulatory surgery.Material and Methods: Observational prospective study of patients submitted to laparoscopic cholecystectomy in ambulatory surgery during a period of 26 months. Data regarding patients’ demography, peri- and postoperative complications, surgical time, time in recovery room, and readmission rates was collected.Results: A total of 231 patients were subjected to Laparoscopic cholecystectomy in the ambulatory unit with overnight stay (time to discharge less than 24 hours). Three patients presented with intra-operative complications, which needed conversion to laparotomy, and four patients were admitted after surgery. The mean time for the procedure was 58 minutes and the mean time for recovery was 19h19 minutes. Postoperative morbidity was 7.8% with 2 nonscheduled admission having occurred.Discussion: One of the controversies regarding laparoscopic cholecystectomy as an outpatient procedure is the need for overnight hospital surveillance. In our unit, we have started LC on an outpatient basis with an overnight stay. Using this protocol, over the past two years, we have operated 231 patients and our results show that this is a completely safe technique.Conclusions: Data from the study suggests that LC is a safe technique when performed in ambulatory practice, having similar results to other european surgical centers.